Range expansion of Procambarus clarkii (Girard, 1852) (Decapoda: Cambaridae) in southern Brazil - Antunes, Mariana [UNESP]; Silva, Alexandre Ribeiro da [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Soc Brasileira Carcinologia, 2020)
The crayfish Procambarus clarkii (Girard, 1852) is a native species from the south-central region of the USA and northeastern Mexico that has been introduced to all continents except Antarctica and Oceania. In Brazil, P. clarkii has 17 established populations, all found in the southeastern region. The studied specimens were obtained at Ribeirao Claro municipality (23 degrees 11'38 '' S 49 degrees 45'28W) in Parana State, southern Brazil, in fish ponds from a private property near the Paranapanema River reservoir. Sampling was performed in September 2013 and March 2015, yielding a total of 13 crayfish specimens. Interviews with residents and workers at the sampling sites revealed that the aquarium trade could be an important introductory pathway, since the first crayfish observed had been released into nature shortly after being purchased at a pet shop in the neighboring state of Sao Paulo; even though current legislation forbids their importation, transportation, and commercialization.
Keywords: Alien biology; ecological plasticity; exotic crayfish; illegal; species expansion